2020
DOI: 10.21873/invivo.12016
|View full text |Cite
|
Sign up to set email alerts
|

A Monocentric Retrospective Observational Study of Comorbidities in Patients Affected by Autoimmune Bullous Diseases

Abstract: Background/Aim: Autoimmune bullous diseases (AIBDs) of the skin and mucosae include a heterogeneous group of chronic diseases, which could be associated with various comorbidities. The purpose of this study was to evaluate the comorbidity profiles of patients affected by AIBDs, who referred to the Dermatological Clinic of Padua from December 2015 to June 2018. Patients and Methods: A monocentric retrospective observational study was conducted on 157 patients with diagnosis of AIBDs. Patients' comorbidities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… 23 28 Similarly, hypertension has been shown to be significantly associated with BP in many case–control studies, 19 24 , 29 but not under all circumstances. 9 , 10 , 25 27 A few studies have shown a negative association between hyperlipidemia and BP, 24 but others have not shown any relationship. 19 , 21 In addition, two large population-based studies conducted in the United States showed a significant association between obesity and BP.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 23 28 Similarly, hypertension has been shown to be significantly associated with BP in many case–control studies, 19 24 , 29 but not under all circumstances. 9 , 10 , 25 27 A few studies have shown a negative association between hyperlipidemia and BP, 24 but others have not shown any relationship. 19 , 21 In addition, two large population-based studies conducted in the United States showed a significant association between obesity and BP.…”
Section: Discussionmentioning
confidence: 93%
“…Many previous studies have shown associations between BP and cardiovascular risk factors, suggesting a possible link between BP and MS. During the past decade, a number of case-control studies 9,10,[19][20][21][22] have shown a strong association between BP and diabetes, whereas others have not. [23][24][25][26][27][28] Similarly, hypertension has been shown to be significantly associated with BP in many case-control studies, [19][20][21][22][23][24]29 but not under all circumstances. 9,10,25-27 A few studies have shown a negative association between hyperlipidemia and BP, 24 but others have not shown any relationship.…”
Section: Discussionmentioning
confidence: 99%